Performance-based fire Protection Design of Ruins Protection Pavilion Based on Air-supported Membrane Structure. (2016) - Zhou, Yang; Sun, Zhuo-er; Gao, Qi
Abstract: At present, air-supported membrane structure is widely applied in the large span space buildings. The stability of air-supported membrane structure and main function of building lead to fire protection design of buildings becomes special and difficult. In this paper, an air-supported membrane structure ruins protection pavilion in Chinese is taken for representative example to analyse the feasibility of fire protection design and propose corresponding solutions of performance-based fire protection. By means of combustion experiment and numerical simulation, carry out fire risk analysis of air-supported membrane structure, smoke spread process and safe evacuation analysis in fire scenes. The results show that, personnel safe evacuation can achieve before the dangerous coming time. It verifies that on the premise of enhancing effective protection of fire protection systems and equipment, the ruins protection pavilion can reach the same safe level that required by the code. That is to say, existing fire protection design is feasible. Both performance-based fire protection design and membrane architecture are more widely applied to the special building, as a result, lots of problems needed to be solved. For this purpose, we hope to provide some reference for related engineering and technical personnel.